Co-Sintering of Spinel-Based Coating/Contact Dual-Layer Structure for Solid Oxide Fuel Cell Cathode-Side Application. Issue 2 (21st February 2023) - Yu, Y. T.; Lin, Y. C.; Li, R. Z.; Cheng, F. P.; Lu, Y.; Zhou, J.; Guan, C. Z.; Wang, J.-Q.
Abstract : A coating/contact dual-layer structure is fabricated via co-sintering in simulated interconnect/coating/contact/cathode test cells. Two different precursors are utilized to form Mn1.25 Co1.75 O4 and Ce-doped Mn1.25 Co1.75 O4 spinel coatings, while a mixture of Mn oxide and Co metal powders is employed as the contact material. After thermal conversion into a dense coating and a porous contact layer at 900 °C in air simultaneously, both test cells exhibit excellent electrical performance during the 1500-h area-specific resistance (ASR) measurement at 800 °C, due to the unique dual-layer structure via co-sintering. The cell with Ce-containing coating precursor shows better cell ASR behavior and lower degradation rate. Cross-sectional observation of the tested cells is conducted to assess the compatibility of the dual-layer structure with adjacent components as well as its effectiveness in inhibiting chromia scale growth and blocking Cr migration from the interconnect to the cathode.